2017
DOI: 10.1016/j.bbr.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inhibition of Anaplastic Lymphoma Kinase rescues cognitive impairments in Neurofibromatosis 1 mutant mice

Abstract: Heterozygous Neurofibromatosis 1 (NF1) loss of function mutations occur in approximately 90% of patients with neurofibromatosis. A major, disabling phenotypic consequence of reduced NF1 function is cognitive impairment; a possibly related behavioral phenotype is impaired sleep. Recent results in Drosophila have demonstrated a genetic interaction between Anaplastic Lymphoma Kinase (Alk) and NF1 for both associative learning and sleep. Inhibition of Alk improves associative learning and sleep in heterozygous NF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Second, sleep or circadian rhythm defects were only observed in flies completely lacking Nf1 gene expression (Bai & Sehgal, ; Williams et al., ). Third, previous studies using Nf1+/– mice revealed no statistically significant abnormalities in circadian rhythms (Weiss, Weber, Torres, Marzulla, & Raber, ). Because Nf1 ‐null mice are not viable, we employed the Nf1 CKO strain to perform a pilot study comparing vigilance states over a 24‐hr period.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Second, sleep or circadian rhythm defects were only observed in flies completely lacking Nf1 gene expression (Bai & Sehgal, ; Williams et al., ). Third, previous studies using Nf1+/– mice revealed no statistically significant abnormalities in circadian rhythms (Weiss, Weber, Torres, Marzulla, & Raber, ). Because Nf1 ‐null mice are not viable, we employed the Nf1 CKO strain to perform a pilot study comparing vigilance states over a 24‐hr period.…”
Section: Resultsmentioning
confidence: 75%
“…Second, sleep or circadian rhythm defects were only observed in flies completely lacking Nf1 gene expression (Bai & Sehgal, 2015;Williams et al, 2001). Third, previous studies using Nf1+/mice revealed no statistically significant abnormalities in circadian rhythms (Weiss, Weber, Torres, Marzulla, & Raber, 2017).…”
Section: Resultsmentioning
confidence: 84%
“…Neurofibromin has not yet been implicated in circadian rhythms in mammals, although it is associated with sleep phenotypes in humans ( Johnson et al, 2005 ; Leschziner et al, 2013 ; Licis et al, 2013 ; Maraña Pérez et al, 2015 ) and with locomotor activity levels in mice ( Weiss et al, 2017 ). Detection of rhythm phenotypes in knockout mice is complicated by the complete Nf1 loss being embryonic lethal (these mice also frequently show exencephaly) ( Lakkis et al, 1999 ), and effects of the mutation may be recessive at the cellular level.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of neurofibromin, the protein product of Nf1 , renders flies largely arrhythmic, indicating that it serves an important function in the circadian system. Subsequent studies also reported sleep abnormalities in humans with Nf1 ( Johnson et al, 2005 ; Leschziner et al, 2013 ; Licis et al, 2013 ; Maraña Pérez et al, 2015 ), but these have not been traced to the circadian system, nor have circadian phenotypes been reported in Nf1 mutant mice despite evidence for altered duration of locomotor activity ( Weiss et al, 2017 ). Mouse Nf1 mutants are only available as heterozygotes, because complete loss of Nf1 is lethal in mice; thus, behavioral analysis of the genetic null has not been possible.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some of these behavioral deficits (exploratory behaviors, learning/memory) were linked to altered dopamine (DA) levels in the hippocampus [Anastasaki, Woo, Messiaen, & Gutmann, ]. Spatial and contextual learning and memory deficits displayed by Nf1 +/– mice in the Morris water maze and fear conditioning, respectively, were also linked to Anaplastic Lymphoma Kinase activity [Weiss, Weber, Marzulla, & Raber, ; Weiss, Weber, Torres, Marzulla, & Raber, ]. Nf1 +/– mice also demonstrated normal associative learning and olfaction, and did not display anxiety‐ or depression‐related behaviors in the elevated plus maze and light/dark box or forced swim assay, respectively [Molosh et al, ; Silva et al, ].…”
Section: Introductionmentioning
confidence: 99%